2021
DOI: 10.3340/jkns.2020.0342
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve and Complications Experience of Oblique Lateral Interbody Fusion : A Single-Center 143 Consecutive Cases

Abstract: Objective : Oblique lateral interbody fusion (OLIF) is becoming the preferred treatment for degenerative lumbar diseases. As beginners, we performed 143 surgeries over 19 months. In these consecutive cases, we analyzed the learning curve and reviewed the complications in our experience. Methods : This was a retrospective study; however, complications that were well known in the previous literature were strictly recorded prospectively. We followed up the changes in estimated blood loss (EBL), operation time, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Vertebral fractures during OLIF surgery are rare and usually the result of endplate injury. [9][10][11] However, similar to this case, vertebral fractures after OLIF without endplate injury have been barely reported. Some authors have reported vertebral fractures after extreme lateral interbody fusion or lateral lumbar interbody fusion applied large cages, but these were coronal plane fractures related to lateral screw fixation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Vertebral fractures during OLIF surgery are rare and usually the result of endplate injury. [9][10][11] However, similar to this case, vertebral fractures after OLIF without endplate injury have been barely reported. Some authors have reported vertebral fractures after extreme lateral interbody fusion or lateral lumbar interbody fusion applied large cages, but these were coronal plane fractures related to lateral screw fixation.…”
Section: Discussionsupporting
confidence: 69%
“…Vertebral fractures during OLIF surgery are rare and usually the result of endplate injury. [ 9 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Owing to these advantages, OLIF can operate in beginners without difficulty. [ 10 ] However, various complications can occur in the OLIF, such as ureter injury, vessel injury, psoas paresis, respectively. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] However, various complications can occur in the OLIF, such as ureter injury, vessel injury, psoas paresis, respectively. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation